2021
DOI: 10.1007/s10903-021-01288-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Pregnancy and Neonatal Outcomes Between Turkish Citizens and Syrian Refugees with High-Risk Pregnancies

Abstract: Refugee women experience more negative pregnancy and neonatal outcomes, such as low birth weight and preterm birth. The aim of the present study was to compare the clinical characteristics and pregnancy and neonatal outcomes between Turkish citizens and Syrian refugees with high-risk pregnancies. This prospective cohort study was conducted between March and December 2020 in Sanliurfa, Turkey. The maternal characteristics and pregnancy and neonatal outcomes were compared between the two groups. In this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Another study investigating specifically SR women with high‐risk pregnancies was in line with our results showing an ≈50% decreased rate of CS compared with native Turkish patients ( P < 0.001) 20 . Additional data from Turkey, which received a large part of SRs in the beginning of the war, confirmed the lower odds of CS 21 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another study investigating specifically SR women with high‐risk pregnancies was in line with our results showing an ≈50% decreased rate of CS compared with native Turkish patients ( P < 0.001) 20 . Additional data from Turkey, which received a large part of SRs in the beginning of the war, confirmed the lower odds of CS 21 …”
Section: Discussionsupporting
confidence: 84%
“…5 Another study investigating specifically SR women with high-risk pregnancies was in line with our results showing an ≈50% decreased rate of CS compared with native Turkish patients (P < 0.001). 20 Additional data from Turkey, which received a large part of SRs in the beginning of the war, confirmed the lower odds of CS. 21 Our study provides additional data regarding specific conditions, where delivery mode is controversial and, thus, dependent on the health care provider-patient relationship.…”
Section: Discussionmentioning
confidence: 81%
“…In the < 20 age group, the 1st minute mean APGAR score (6.91 ± 0.69) was signi cantly lower than that in the other age groups (p < 0.001). While neonatal NICU admission rates were higher in the < 20 age group (7.1%) than in the other two groups (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)4.49% and > 35, 4.20%), there was no signi cant difference (p = 0.12).…”
Section: Resultsmentioning
confidence: 86%
“…This difference is due to the different regional distribution and socio-cultural levels of Syrian refugees. In a similar study, Sayili et al (21) found that Syrian refugees had a considerably greater parity than Turkish citizens (p=0.010) and a significantly shorter first gestational age (p=0.034).…”
Section: Discussionmentioning
confidence: 83%